Notas sobra a nova lâmina áurea de Tiras do Norte de Portugal - Ladra, Lois; Silva, Armando Coelho F.; Sousa, Maria José (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Notes about a new golden striated and cut plate from an unknown site of the North of Portugal. One describes the object, documents his parallels and discusses the morphological, technological, functional and contextual aspects of this typical jewellery of the Initial Bronze Age with recognized Atlantic dispersion.